Pandangan Orang Tua Terhadap Penentuan Batas Usia Minimal dan Maksimal Pernikahan pada Perempuan di Kelurahan Lok Bahu - Dini, Rahma; Sofyan, Akhmad (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2021)
Differences in parents' views on determining the minimum and maximum age limits for marriage for women in Lok Bahu Village.Parents have different views on determining the minimum age limit for marriage for women in terms of the level of education they have. The minimum age limit set by parents is 17-19 years and the maximum age is 28-30 years. The minimum age limit for marriage is regulated in Law Number 16 of 2019 concerning Marriage, which is to be 19 years old for both men and women. Based on this, the researchers formulated the problem of how the views of parents with low and high education on determining the minimum and maximum age limits for marriage for women in Lok Bahu Village and what factors influence parents in determining the minimum and maximum age limits for marriage for women in Lok Bahu. This study uses empirical legal research, namely research obtained from experience, discoveries, and observations made to obtain field data. The qualitative data analysis technique used in this study uses data analysis techniques according to Miles and Huberman including, collecting data, reducing data, presenting data and drawing conclusions from the data obtained. Thus, it is hoped that the community will prioritize the level of education first before marrying off their daughters.